2011
DOI: 10.1590/s1413-81232011001100021
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and the nutritional status of preschool children: a spatial analysis

Abstract: Dental caries and the nutritional status of preschool children -a spatial analysisCárie dental e estado nutricional de pré-escolares -análise espacial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…21,22 Such results may be explained by the fact that different populations have a different food culture, which influences the prevalence of childhood overweight/obesity. The association between these two conditions has not been observed in previous studies with Brazilian children 34,35 and pre-adolescents. 35,36 We could not observe a statistical association between overweight/obesity and dental caries, nor between underweight and dental caries.…”
Section: Discussioncontrasting
confidence: 61%
“…21,22 Such results may be explained by the fact that different populations have a different food culture, which influences the prevalence of childhood overweight/obesity. The association between these two conditions has not been observed in previous studies with Brazilian children 34,35 and pre-adolescents. 35,36 We could not observe a statistical association between overweight/obesity and dental caries, nor between underweight and dental caries.…”
Section: Discussioncontrasting
confidence: 61%
“…Of the 64 publications analysed, three 25‐27 reported results from two countries, so data were entered separately for each country, giving a total of 67 prevalence estimates. The studies reported results from Africa 25,28‐32 (n = 7), Americas 33,33,33,34,34,34,35,35,35,36,36,36‐57 (n = 27), Asia 58‐82 (n = 27), Europe 26,83‐86 (n = 5), and Oceania 87 (n = 1). The studies analysed included 59,062 patients in total, with an average sample size (standard deviation) of 881(1189).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that systematic home nutritional advice during the first year of life can decrease the incidence of dental caries by 22% in 4-year-old children [48]. Although a sample from two health districts of a large city in Brazil was studied, the results are likely generalizable because a stratified sample was selected and because dental caries and obesity are health conditions that are not spatially dependent [49]. …”
Section: Discussionmentioning
confidence: 99%